El procedimiento directo en los Delitos de Hurto y su incidencia en el principio de Celeridad en las Sentencias emitidas por los Jueces de la Unidad Judicial Penal del cantón Riobamba en el período agosto - septiembre 2014 - Bolagay Larrea, Priscila Andrea (2015)
This research paper mentions the direct procedure in the theft offences and its impact on the principle of foot-dragging in the judgments issued by the judges of the Criminal Court unit based in Riobamba canton, in other words analyze the advantages and disadvantages of the direct procedure and its influence on the promptness principle. The structure of this research is divided into four chapters: Chapter one, is about the frame of reference where the problem approach, its origin, the general objective and specific objectives to determine if the direct in the theft offences procedure gives rise to an incidence of legal at the beginning of quickly issued statements by the criminal justice unit based in Riobamba canton, also the rationale and importance of the problem where we note that this investigative work is feasible, innovative, and original. Chapter two, develops the theoretical framework, where it is applied the signing instrument which received doctrine, theories, concepts, and bibliographic items drawn from books, laws, regulations and texts, this comes to build the theoretical, conceptual, legal and doctrinal part of the research. This chapter is divided into four units and subunits. The first unit talks about the direct procedure, definition, doctrinal concept, when comes the direct procedure, in which crimes should be the direct procedure, duration of the direct procedure, suspension and deadline for submitting evidence in the direct procedure, the procedure of direct benefits and disadvantages of the direct procedure in which will discuss fundamental concepts that will help to focus on the research, The second unit discuss crime of theft which will develop definitions, differences between robbery and theft, as well as in relation to the COIP theft; in the third unit talks about the principle of procedural haste, in which we will cover conceptualizations, nature, scope, objective of the rapidity in the direct procedure principle, and we will analyze the influence of the principle of foot-dragging in the principle of judicial economy; the fourth unit talks about the incidence of the direct procedure in the beginning of foot-dragging in the judgments issued by the judges of the Criminal Court unit based in Riobamba canton , hypothetical unit, hypothesis, variables operationalization. Chapter three, the methodological framework is developed, using the inductive method: through the use of this method be accomplished to study the problem from the particular to the general where analysis on the impact of the direct procedure will take place at the beginning of foot-dragging in the judgments issued by the judges of the Criminal Court unit based in Riobamba canton; as well as the application of interviews that was used a direct discussion with the judges of the Criminal Court unit based in Riobamba canton, performing it with the entire population, was used with the inductive method interview guide; through the interview and the inductive method, it could be gotten the information that helped to identify the incidence of legal principle of foot-dragging in the direct procedure in any way. Chapter four, provides the conclusions and recommendations obtained by research through the interpretation and discussion of the results made through pictures and graphical statistics, with the help of the software package of EXCEL in which the results are gotten in exact percentages for the data processing, this is a descriptive research since then of tabular interpret and information process, described the problem as it appears, behaving in their context and explaining the result after tabulated and calculated. Finally, Chapter five contains the bibliography, supplementary bibliography, internet sources and annexes.